Clustering of HTLV-1 associated myelopathy/tropical spastic paraparesis (HAM/TSP) and infective dermatitis associated with HTLV-1 (IDH) in Salvador, Bahia, Brazil - Silva, José Lucas Sena da (2013)
Texto completo: acesso restrito. p. 482–485